Centrifuge modelling of tunnelling with forepoling. Issue 2 (16th October 2015) - Divall, Sam; Taylor, R. Neil; Xu, Ming
Abstract : Geotechnical centrifuge modelling provides a means by which geotechnical events and processes can be better understood. In particular, the technique has proved invaluable when investigating collapse mechanisms in small-scale models that can be related to full-scale events. A series of eight plane strain centrifuge model tests investigating the effect of inserting inclusions around the annulus of a single tunnel in overconsolidated clay have been conducted using the geotechnical centrifuge at City University London. The model used a compressed air-supported circular cavity to simulate the tunnel. Stiff resin inclusions embedded around its periphery were used to represent closely spaced forepoles forming grout umbrella arches. Image processing was used to obtain patterns of displacements at the subsurface and displacement transducers measured vertical settlement at the ground surface level. The investigation focused on how different arrangements of forepoling affected tunnel stability. The influence of forepoling on normally accepted plastic collapse mechanisms is discussed. An optimisation of the forepoling layout is suggested in accordance with the findings.